Finanças comportamentais: um estudo sobre a confiabilidade das decisões dos investidores, analistas e profissionais de investimento à luz da metodologia brier score - Pimenta, Daiana Paula (2009)
Behavioral Finance is a new field of study which is opposed to the assumption of decisionmakers rationality adopted by modern finances. One of the aspects of the studies in behavioral finance is to identify how emotions and cognitive failures may influence the individual decision making process. Economic psychology shows the use of heuristics and biases resulting from these failures, among which bias of overconfidence can be highlighted. This work aims to study and learn more about the influence of socio-demographic characteristics and possible cognitive failures made by investors, analysts and investment professionals from the state of Minas Gerais, Brasil during their decision-making, relating empirical findings to behavioral finance theories. Therefore the answer to the following questions is proposed: In what ways do the characteristics of the socio-demographic profile and excess of confidence influence the decisions of investors, analysts and investment professionals of the state of Minas Gerais, Brasil? What level of reliability is evident in these decisions? For this survey, a virtual questionnaire of 32 questions was chosen. Contact with these individuals was made possible through a partnership signed with the Association of Investment Analysts and Investment Capital Market of Minas Gerais - MG APIMEC and the securities market broker, TBC Investments, which invited, via email, their members to fill out the questionnaire on-line on a determined Internet Site. Data analysis was performed using two estimation methods: least squares Two-stage (2SLS) and ordinary least squares (OLS), resistant to heteroskedasticity and corrected for finite population. The results of this empirical study suggested that differences of opinion, style and perception of reality motivated by personal characteristics and investments and susceptibility to bias of overconfidence of agents exert significant impact on decision making and thus contribute to greater or lesser reliability of this process. This work is believed to have contributed to the making of financial decisions of the studied agents to be more likely to produce satisfactory results, as awareness of the influence of traits, survey participants will tend to seek strategies to address the deficiencies and improve the process of decision making.